Pengaruh Brand Awareness dan Brand Image terhadap Keputusan Pembelian Tas Merek Charles and Keith pada Konsumen di Kecamatan Medan Johor - Lubis, Febby Yohana; Marbun, Patar; Royani, Ida; Siregar, Muhammad Yamin (Prodi Bisnis Digital Universitas Pahlawan Tuanku Tambusai, 2025)
This study is motivated by the rapidly evolving fashion industry and the critical need to understand consumer behavior in choosing branded bags such as Charles & Keith, highlighting the urgent need to identify key determinants of purchase decisions including brand awareness and brand image. The tested hypothesis posits that both variables jointly and individually influence purchase decisions. Employing a quantitative approach with multiple linear regression analysis, the study surveyed 50 respondents selected through purposive sampling from Charles & Keith bag consumers in Medan Johor District. The hypothesis testing revealed that brand awareness has no significant effect (t = –0,111; p = 0.912), whereas brand image exerts a positive and significant influence (t = 3.559; p = 0.001), indicating that perceptions of quality, design, and brand reputation are the primary drivers of consumer purchase decisions. These findings underscore the importance of enhancing brand image in marketing strategies. Therefore, producers and business owners should focus on improving product quality, aesthetics, and communication to strengthen brand image among consumers.